Pembudayaan Mazhab Syafi'i dalam Masyarakat Islam di Malaysia - Awang, Idris; Tengku Kasim, Tengku Sarina Aini (Jurnal Fiqh, 2007)
The paper attempts to look into the process of enculturisation of Shafi'ite school of thought in education and Islamic law from the early period of Islam in the peninsular Malaya. The first part of the paper focuses on the process of educating Islamic law, formal and informal, followed by the practice of Islamic law in the country. The final part attempts to analyze the influence of websites, books and idealism in the future practice of Shafi'ite school in Malaysia.